Investigating the cross currency basis in EURUSD and EURGBP - Thomas Heidorn; Nekruz Mamadalizoda (Frankfurt School of Finance & Management, 2019)
The fundamental premise upon which the pricing of major FX derivatives rests is the Covered Interest Parity (CIP), and a violation is seen as a reflection of potential capital market inefficiencies. CIP postulates that FX forward prices simply reflect the interest rate differential between the two currencies. This has been the case before the global financial crisis. During the 2008 financial and 2011 European debt crises, market prices deviated significantly from the theoretical CIP-implied prices, and the deviations persist at noticeable levels until present. This paper documents and analyzes the pronounced nature of the EURUSD and EURGBP CIP violations from 2007 to 2019. We explain the basis in terms of five driving factors: credit risk differential, funding liquidity differences, measurement error, hedging demand imbalance, and new constraints to arbitrage. Furthermore, we carry out a term structure analysis, showing the varying dynamics of CIP violations across maturities and over time. Lastly, we test a statistical approach to adjust the interest rate differential formula bringing the theoretical prices closer to market (i.e., reducing CIP deviation).
Keywords: E30; E42; E44; G15; 330; cross-currency basis; covered interest parity; CIP deviation; EURUSD basis; EURGBP basis; FX swaps; FX forwards; cross-currency basis swaps